Analysis of Legal Sociology Policy Regional Spatial Planning (RTRW) Boulevard Tondano, Minahasa Regency - Cynthia Maria Siwi; Obed Bida; Jeane Mantiri; Romi Mesra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Regulating spatial use in regency areas is governed by Regional Regulation No. 1 of 2014 concerning Spatial Planning for the Minahasa Regency Area, which serves as a guideline for the execution of spatial use regulation in regency regions. The purpose of this study was to examine the implementation of the Spatial Policy for the Tondano Boulevard Area, Minahasa Regency. A qualitative research methodology was used in this study. The study findings show that the use of space is not in accordance with its designation and management. Lack of dissemination of local regulations by the government. Lack of government control and oversight. Lack of understanding, as well as community responsibility. No harsh consequences are made for rule breakers. The findings of this research are expected to be a source for academics, particularly in the fields of sociology, politics, law and state administration, as well as for the general public.